743 THE THIRD NATIONAL SURVEY OF UNDERGRADUATE TEACHING IN AGEING AND GERIATRIC MEDICINE AND ITS IMPACT ON STUDENTS' ATTITUDES. (8th March 2022) - Pearson, G M E; Blundell, A G; Gordon, A L; Masud, T; Ben-Shlomo, Y; Henderson, E J
Abstract: Introduction: The British Geriatrics Society's (BGS) recommended undergraduate curriculum was conceived in 2008 and mapped to the General Medical Council's (GMC) standards [1]. Subsequently, two national surveys have described how geriatric medicine is taught in the UK and both identified areas for improvement [2, 3]. In 2018, the GMC updated their statutory learning outcomes, therefore it is timely that the BGS remap their curriculum to this new guidance, with repeat surveys of UK institutions and students. Methods: We will undertake a three-stage study of undergraduate education in geriatrics. Firstly, we will map the BGS recommended curriculum to the GMC's 'Outcomes for Graduates'. Secondly, we will survey UK medical schools on the content, methodology, timing and duration of teaching in geriatrics. Thirdly, we will assess medical students' attitudes towards older people and a potential career in geriatric medicine. Results: Descriptive analysis will be used for quantitative data. 'White space' questions will be analysed qualitatively using a framework approach. Medical school data will be compared to the BGS recommended curriculum to identify gaps in the current provision of education in geriatrics. We will test whether teaching exposure to geriatrics is associated with students' attitudes and career intentions, conditional on student characteristics. Conclusion: In order to meet the demands of the ageing population, it is essential that medical schools nurture doctors furnished with the knowledge, skills and values required to look after older adults with complex care needs. This study is an opportune evaluation of current UK teaching provision and student attitudes that will inform future iterations of the BGS recommended undergraduate curriculum and innovations in geriatric medicine education. References: 1. Forrester-Paton C, Forrester-Paton J, Gordon AL et al. Undergraduate teaching in geriatric medicine: mapping the British geriatrics society undergraduate curriculum to Tomorrow's doctors 2009. Age Ageing 2014; 43: 436–9. 2. Gordon AL, Blundell AG, Gladman JRF, Masud T. Research letter. Age Ageing 2010; 39: 385–8. 3. Gordon AL, Blundell AG, Dhesi JK et al. UK medical teaching about ageing is improving but there is still work to be done: the second National Survey of undergraduate teaching in ageing and geriatric medicine. Age Ageing 2014; 43: 293–7.